Chapter 5 Regional tectonics, structure and evolution of the Andaman–Nicobar Islands from ophiolite formation and obduction to collision and back-arc spreading - Morley, C; Searle, M (Geological Society of London, 2017)
Published by The Geological Society of London. A wide range of tectonic models exist for the Cretaceous-Cenozoic development of the Sumatra-Andaman- Myanmar region, reflecting outstanding regional issues including: (1) suture zone correlation between Tibet and Myanmar; (2) understanding ophiolitic fragment emplacement; (3) timing of ophiolite emplacement; (4) tectonic setting of ophiolite formation; (5) post-emplacement ophiolite history; (6) number, distribution and accretion timing of different tectonic continental blocks in western SE Asia; (7) how the Andaman-Sumatra subduction zone developed during the Cenozoic, and location and timing of inactive, v. obliquely subducting segments; and (8) considerable variations in regional plate tectonic reconstructions (e.g. latitude of Lhasa Block at the time of collision, amount and direction of block rotation within SE Asia). Following reviews of these issues we propose a relatively simple model whose characteristics are continuity of a single continental mass between Myanmar and Sumatra during the Cenozoic, early Cenozoic ophiolite emplacement as imbricate slices within an accretionary complex and no emplacement of a major overthrusting oceanic slab. Subsequent collisional deformation further dismembered the ophiolites. Approximately 30° clockwise rotation of SE Asia occurred following Asia-India collision, accompanied by transition from a paired Andean-type magmatic belt to regional oblique-slip and strike-slip tectonics. During the Neogene the Andaman sea region became dominantly transtensional, while Myanmar in the Late Neogene became transpressional.